2018
DOI: 10.1002/cne.24576
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic distributions of pS214‐tau in rhesus monkey prefrontal cortex are associated with spine density, but not with cognitive decline

Abstract: Female rhesus monkeys and women are subject to age‐ and menopause‐related deficits in working memory, an executive function mediated by the dorsolateral prefrontal cortex (dlPFC). Long‐term cyclic administration of 17β‐estradiol improves working memory, and restores highly plastic axospinous synapses within layer III dlPFC of aged ovariectomized monkeys. In this study, we tested the hypothesis that synaptic distributions of tau protein phosphorylated at serine 214 (pS214‐tau) are altered with age or estradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 169 publications
(319 reference statements)
1
2
0
Order By: Relevance
“…Therefore, we sought to understand perisynaptic alterations that could render synapses dysfunctional and may distinguish individuals that age without cognitive impairment from those that age with cognitive impairment. Consistent with prior work in aged macaques (Cork et al, 1990;Crimins et al, 2019), we found that aged marmoset presynaptic boutons were larger than young. Furthermore, congruent with the ultrastructural size principle and prior work in aged macaque dlPFC, there were strong linear relationships between synapse and bouton sizes in each of the marmosets.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we sought to understand perisynaptic alterations that could render synapses dysfunctional and may distinguish individuals that age without cognitive impairment from those that age with cognitive impairment. Consistent with prior work in aged macaques (Cork et al, 1990;Crimins et al, 2019), we found that aged marmoset presynaptic boutons were larger than young. Furthermore, congruent with the ultrastructural size principle and prior work in aged macaque dlPFC, there were strong linear relationships between synapse and bouton sizes in each of the marmosets.…”
Section: Discussionsupporting
confidence: 92%
“…6F) (7,40). In young monkeys, there is delicate pS214Tau labeling in axons (40), and in the PSD that appears to play a beneficial role (81). However, the large aggregations of pS214Tau near the synapse in aging (7, 40) may interfere with synaptic transmission.…”
Section: Aging Rhesus Monkeys: Unique Opportunity To Study the Etiolomentioning
confidence: 99%
“…At the ultrastructural level, young macaques (9–11 years, n = 3) showed higher incidence of p‐S214 tau in axons and proximal dendrites, whereas in old macaques (24–31 years, n = 5), it was predominant within dendritic spines, suggesting age‐related trafficking of phosphorylated tau (Carlyle et al, 2014). Moreover, p‐S214 tau within axon terminals and dendritic spines in female rhesus macaques was reduced with age (young 9.9 ± 0.7 years, n = 8 vs. old 25.2 ± 0.9 years, n = 8) and correlated with synapse density but not cognitive status (Crimins et al, 2019).…”
Section: Cercopithecidsmentioning
confidence: 99%